Utilizing Solar Power for Communication and Illumination in Disaster Zones: Listrik untuk Komunikasi dan Penerangan di Lokasi Bencana (Sun-Power) - Jamaaluddin Jamaaluddin; Izza Anshory; Septi Budi Sartika; Khoiri; Mardiyono (Academia Open, 2023)
Abstract Natural disasters often occur on this earth, especially in Indonesia. There are several types of disasters that occur, namely: geological disasters, hydrometeorological disasters and others. This natural disaster caused quite a lot of casualties and not a few material. Good post-natural disaster management is necessary to minimize the number of victims of a disaster. One form of handling this natural disaster is by providing electrical energy that can be used to provide lighting and communication systems. The provision of electrical energy consists of several integrated systems to form a compact, simple and efficient unit. This tool consists of a Solar Power Generation system, GenSet system, inverter system, Change Over Switch system and Global Positioning System system. This tool is named SUNPO which stands for Sun Power or Solar Power. With this SUNPO, it can function as a power supply to power direct current loads and alternating current loads. If the solar power is not enough to charge the battery then the system can be operated with a GenSet. Meanwhile, to find out the position of SUNPO, a Global Positioning System is also installed. Highlights: Effective Disaster Response: Efficient post-disaster management is crucial to minimize casualties and damage caused by natural disasters, especially in Indonesia. SUNPO Tool Integration: The SUNPO (Sun Power) tool integrates solar power generation, GenSet backup, inverter, changeover switch, and GPS systems to provide a reliable and compact solution for electricity supply in disaster-stricken areas. Dual Power Source: SUNPO offers dual power sources - solar energy and GenSet - ensuring continuous electricity supply for both direct and alternating current loads, enhancing communication and lighting systems for affected communities. Keywords: Natural disasters, Post-disaster management, SUNPO, Solar Power, Global Positioning System.